2005
DOI: 10.1038/sj.emboj.7600744
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ spikes in the flagellum control chemotactic behavior of sperm

Abstract: The events that occur during chemotaxis of sperm are only partly known. As an essential step toward determining the underlying mechanism, we have recorded Ca 2 þ dynamics in swimming sperm of marine invertebrates. Stimulation of the sea urchin Arbacia punctulata by the chemoattractant or by intracellular cGMP evokes Ca 2 þ spikes in the flagellum. A Ca 2 þ spike elicits a turn in the trajectory followed by a period of straight swimming ('turn-andrun'). The train of Ca 2 þ spikes gives rise to repetitive loop-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
246
1
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(257 citation statements)
references
References 36 publications
8
246
1
2
Order By: Relevance
“…Sperm chemotaxis of marine invertebrates requires the strict coupling of the Ca 2+ oscillations with the direction or polarity of the chemoattractant gradient (Böhmer et al, 2005;Shiba et al, 2008;Guerrero et al, 2010a;Kashikar et al, 2012). We found that L. pictus spermatozoa are able to suppress the onset of Ca 2+ fluctuations while swimming toward the center of a speract gradient.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Sperm chemotaxis of marine invertebrates requires the strict coupling of the Ca 2+ oscillations with the direction or polarity of the chemoattractant gradient (Böhmer et al, 2005;Shiba et al, 2008;Guerrero et al, 2010a;Kashikar et al, 2012). We found that L. pictus spermatozoa are able to suppress the onset of Ca 2+ fluctuations while swimming toward the center of a speract gradient.…”
Section: Introductionmentioning
confidence: 76%
“…The relationship between the timing of the [Ca 2+ ] i fluctuations and the shape of the chemical gradient determines the positioning of the turn-and-run motility response (Böhmer et al, 2005;Shiba et al, 2008;Guerrero et al, 2010a;Guerrero et al, 2010b;Kashikar et al, 2012). Supplementary material Fig.…”
Section: Nfa Disrupts Sperm Chemotaxismentioning
confidence: 99%
See 1 more Smart Citation
“…Ca 2+ plays a key role in the regulation of fl agellar beating, and in the case of sea urchin spermatozoa, the sperm attractant triggers [Ca 2+ ] i fl uctuations (Böhmer et al 2005 ;Wood et al 2005 ) that appear to correlate with the asymmetrical beating of sperm fl agella (Brokaw et al 1974 ;Brokaw 1979 ). In the hydrozoan siphonophore s, the diameters of the sperm trajectories decrease on approach of the sperm to the cupule (a spermattracting accessory organ of the egg), but the sperm trajectories are unchanged in the absence of Ca 2+ (Cosson et al 1984 ).…”
Section: Ca 2+ Changes Mediate Sperm Chemotaxismentioning
confidence: 99%
“…Chemoattractants such as "resact " in sea urchins (Ward et al 1985 ;Guerrero et al 2010 ), "sepsap " in cuttlefi sh (Zatylny et al 2002 ), and "asterosap " in starfi sh (Böhmer et al 2005 ) are peptides. A 21-kDa protein named "allurin " in the amphibian Xenopus laevis (Olson et al 2001 ) and tryptophan in abalone (Riffell et al 2002 ) act as sperm chemoattractants.…”
Section: Chemical Nature Of Sperm Chemoattractantsmentioning
confidence: 99%